2009
DOI: 10.1097/ta.0b013e3181715dba
|View full text |Cite
|
Sign up to set email alerts
|

Acute Subdural Hematoma Because of Boxing

Abstract: Our study shows that ASDH because of boxing is characterized by bleeding from bridging or cortical veins, and that the site of bleeding is a significant determinant of their prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…15) The source of bleeding in boxers with ASDH was also either a bridging or a cortical vein. 26 , 27) Laceration of large bridging or cortical veins may exacerbate cerebral perfusion by venous congestion or infarction, resulting in brain swelling. 37) Hits directed eccentrically to the head of boxers produce rotational acceleration.…”
Section: Sports-related Asdhmentioning
confidence: 99%
“…15) The source of bleeding in boxers with ASDH was also either a bridging or a cortical vein. 26 , 27) Laceration of large bridging or cortical veins may exacerbate cerebral perfusion by venous congestion or infarction, resulting in brain swelling. 37) Hits directed eccentrically to the head of boxers produce rotational acceleration.…”
Section: Sports-related Asdhmentioning
confidence: 99%
“…In boxing, acute TBI can be caused by a minimal (no loss of consciousness, Glasgow Coma Scale (GCS) of 15), mild (history of loss of consciousness, GCS [14][15] or moderate/severe TBI (associated with e.g. subdural haematoma and intra-cerebral haemorrhage) [1][2][3][4]. TBI may be associated with knock-out (KO) with loss of consciousness, but may also be caused by the cumulative effect of sub-concussive translational and rotational punches to the head [5].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the patient's papilledema was likely caused by boxing trauma leading to a chronic SDH and persistent increased intracranial pressure. Kushi et al (5) showed that SDH from boxing injuries are more likely to occur in younger patients, have longer lucid intervals, lack skull fractures or cerebral contusions, and involve trauma to the bridging and cortical veins; however, all patients in this study had acute SDH and initially presented with altered consciousness or headache.…”
mentioning
confidence: 58%